Aksaray Koçaş Tarım İşletmesinde yetiştirilen holştayn düve ve ineklerde tohumlama yaşı ile gebelik oranı arasındaki ilişki (Relationship Between Insemination Age and Pregnancy Rate in Holstein Heifers and Cows Raised in Koçaş State Farm in Aksaray) - Türk, G (My University, 2010)
This study was conducted to determine relationship between insemination age and pregnancy rate in Holstein heifers and cows. In the study, data regarding to the Holstein heifers and cows raised in Koçaş State Farm in Aksaray were used. According to the investigated records, 100 healthy heifers and 900 cows which were free of reproductive disorders and did not expose to the any reproductive drugs were divided into 4 groups according to their ages. One hundred heifers at 15 months of age in Group1, 300 cows at 2-3 years of age in group 2, 300 cows at 3-4 years of age in group 3 and 300 cows at 4-5 years of age in group 4 were artificially inseminated by rectovaginal method using 0.25 ml straws including frozen-thawed bull semen at second half of the oestrus. Pregnancies of animals were determined by rectal palpation on day 50 after inseminations. Pregnancy rates in group 1, 2, 3 and 4 were determined as 51%, 45%, 38% and 21%, respectively. Average pregnancy rate obtained all the groups were 36.3%. A significant negative correlation (r= -0.914, P<0.001) was found between animal age and first insemination pregnancy rate. According to the results of farm data, it was judged that as the age progress, a decrease occurs in the pregnancy rate in Holstein cattle at 15 months-5 years old.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Yaş gebelik suni tohumlama inek düve (Age pregnancy artificial insemination cow heifer)